2015
DOI: 10.1002/lno.10125
|View full text |Cite
|
Sign up to set email alerts
|

Chemical mixing in the bottom boundary layer of a eutrophic reservoir: The effects of internal seiching on nitrogen dynamics

Abstract: In lakes and reservoirs, the bottom boundary layer (BBL) mediates chemical fluxes between sediments and the overlying water column. At the internal shoreline, where the thermocline contacts the lakebed, the motions of internal waves can create fluctuating redox conditions and dynamic physical forcing that may support ecologically important reactions such as denitrification. We characterized physical and chemical dynamics within the internal shoreline of a eutrophic reservoir during the spring and early summer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 45 publications
2
27
0
1
Order By: Relevance
“…Conversely negative DT/D z, which indicates unstable stratification, with a mean value of 20.058C m 21 (Figure 7b) occurred at the peak of positive <V> or negative d<T>/dt (Figures 7e and 7f), i.e., during the colder up-slope flow phase. Similar Water Resources Research 10.1002/2015WR017725 synchronization between benthic <V> and DT/D z has recently been observed by Deemer et al [2015] at the depth of the thermocline of a small lake.…”
Section: 1002/2015wr017725supporting
confidence: 72%
See 1 more Smart Citation
“…Conversely negative DT/D z, which indicates unstable stratification, with a mean value of 20.058C m 21 (Figure 7b) occurred at the peak of positive <V> or negative d<T>/dt (Figures 7e and 7f), i.e., during the colder up-slope flow phase. Similar Water Resources Research 10.1002/2015WR017725 synchronization between benthic <V> and DT/D z has recently been observed by Deemer et al [2015] at the depth of the thermocline of a small lake.…”
Section: 1002/2015wr017725supporting
confidence: 72%
“…Similar synchronization between benthic < V> and ΔT/Δz has recently been observed by Deemer et al . [] at the depth of the thermocline of a small lake.…”
Section: Results and Observationsmentioning
confidence: 99%
“…The resulting intermittent instability drives free convection and accelerates the fluxes at the sediment-water interface by more than 1 order of magnitude, as experimentally observed by Kirillin et al (2009), Lorke et al (2005) and Chowdhury et al (2016). In lakes with anoxic water layers, the seiche-induced oscillations can be accompanied by periodical changes in the oxygen concentration in a large internal shoreline area as described by Deemer et al (2015) for Lacamas Lake. Bernhardt et al (2014) observed similar seiche-induced oxygen fluctuations at the sediment-water interface in the shallower area of the eutrophic Lake Arendsee resulting from the formation of a distinct metalimnetic oxygen minimum during summer.…”
Section: Introductionmentioning
confidence: 72%
“…BBLs may be responsible for much of the vertical mixing of density, nutrients, and pollutants in lakes [ Goudsmit et al ., ; Wüest and Lorke , ] and may also play an important role in the vertical mixing of some estuaries [ Inall , ]. Further interest in internal wave BBLs is motivated by their influence on sediment transport [ Pierson and Weyhenmeyer , ] and sediment‐water biogeochemical fluxes [ Lorke et al ., ; Holtappels et al ., ; Deemer et al ., ].…”
Section: Introductionmentioning
confidence: 99%